The Effect of Dividend Policy on Stock Market Price Volatility of Banks in the Gulf Cooperation Council (GCC) Markets: (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2022)
This study examined the effect of dividend policy on the stock market price volatility of banks in the GCC markets. The study data were obtained from the annual financial reports and accounts of the selected sampled banks. The study used the panel data analysis fixed effect regression model.  The findings revealed that dividend yield and dividends payout does not influence the market share price in the GCC market. Therefore, they do not affect the GCC banks’ market share price, thus the findings of the study support the dividend policy irrelevance theory.  The study recommends that managers in the GCC banks should focus on and emphasize allocating more funds in investment rather than paying dividends. The findings have important practical implications for the policymakers on dividends in the GCC banks due to unstable and inconsistent trends of dividend payments and making it difficult for shareholders on dividend policy decisions predictions